PENGARUH KREATIVITAS DAN MOTIVASI TERHADAP KEBERHASILAN USAHA DI DESA AMURI KECAMATAN LOLOWAU KABUPATEN NIAS SELATAN - Niashinta Elsa Pertiwi Laia (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
The aim of this research is to determine the influence of creativity and motivation on business success in Amuri Village, Lolowau District, South Nias Regency. This type of research is quantitative. The population and sample in this research were 32 respondents. The type of masukan for this research is primary masukan, namely masukan obtained directly from respondents. The masukan source for this research is from business actors using artistik questionnaire. The masukan analysis method used is multiple regression analysis. Based on the research results, it was determined that there was artistik simultaneous influence of creativity and motivation on business success in Amuri Village, Lolowau District, South Nias Regency. The suggestions for this research are (1) In sistem to increase business success, every entrepreneur should have the ability to creatively manage their business, each product must be available on site so that sales can run effectively. (2) Every entrepreneur who has the motivation to achieve success in entrepreneurship should accept every comment from customers to renew his entrepreneurship. (3) Promoting products is a good way to expedite business so that business success can increase to the maximum.